The effectiveness of health education program on knowledge of coronary heart disease (CHD) among public in Puncak Alam, Selangor / Raja Anis Raja Ismail, Amirah Farhanah Kamaruddin and Norzulaikha Darulikhsan - Raja Ismail, Raja Anis; Kamaruddin, Amirah Farhanah; Darulikhsan, Norzulaikha (2016)
Background: Globally, coronary heart disease (CHD) is the leading cause of death. In time, death due to CHD will be increased progressively. According to WHO (2014) CHD death in Malaysia has reached 23.10% or 29 363 of total deaths. CHD happened due to atherosclerosis that deposited inside the wall of the arteries which results in the insufficient of blood supplies inside the body. Objective: The aim of this study is to assess the effectiveness of health education program on knowledge of CHD among public in Puncak Alam, Selangor. Methods: Quasi-experimental study was conducted by giving out questionnaires to 57 respondents. Firstly, pre-questionnaires were provided to public before the health talk and was collected instantly. After health talk given, post-questionnaires were distributed and also collected immediately. Participants were given about 10-15 minutes to complete the pre and post-questionnaire. The result was then classified into an acceptable and a good level of knowledge. The data was analysed by using a descriptive analysis and Mc Nemar test was used to compare level of knowledge pre and post-test whereas non-parametric chi square was used to determine the relationship between level of knowledge and demographic data. Results: The result of this study showed that in pre-test majority of the participants 66.7% (n=38) had an acceptable knowledge (<70%) regarding CHD whereas 33.3% (n=19) of the participants had a good level of knowledge (70%-100%). In post-test, 73.7% (n=42) of the participants were reported as having a good level of knowledge and the remaining, n=15 (26.3%) had an acceptable knowledge. Pre-test showed that majority of the participants were basically having an acceptable level of knowledge compared to post-test with (p=0.001). However in post-test it was described majority of the participants had a good level of knowledge compared to pre-test with (p=0.001). In addition, there was a relationship between level of knowledge and demographic data including gender (p=0.024), education level (p=0.019) and family history (p=0.024). Conclusions: This research proved general knowledge of public at an acceptable knowledge during pre-test and increase to a good level of knowledge in post-test after giving health education. Health education provides a major impact to the public by increasing their level of knowledge. Therefore, educational program on cardiac health should be increased because it is one of the best medium to provide an input to the public; at the same time it will increase level of knowledge and awareness towards the disease.